The radical right in Switzerland : continuity and change, 1945 - 2000 - Skenderovic, Damir 1965- (Berghahn Books, 2009)
The concept of the radical right -- Success conditions and organisational variation in Switzerland -- An early precursor : the movement against overforeignization in the 1960s and 1970s -- Outsiders in the party system : fringe parties in the 1980s and 1990s -- Entering the mainstream : the emergence of the new SVP in the 1990s -- A supplier of ideology : the new right in the German-speaking part of Switzerland -- An intellectual elite : the new right in the French-speaking part of Switzerland -- At the margins of society and politics : the subculture of the extreme right